2018
DOI: 10.1080/09593330.2018.1481889
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the ultrasound effect on treated municipal wastewater

Abstract: In this research, ultrasound (US; 26 kHz) application was evaluated as tertiary treatment of treated municipal wastewater coming from conventional activated sludge (AS) and constructed wetland (CW) systems. The degree of disinfection was evaluated through the total (TC) and faecal (FC) coliforms and by somatic coliphages (SCs) determinations. The experiments were carried out without temperature control at times of 200, 400 and 600 s and with temperature control (298.1 K) at 600, 1200 and 1800 s. Changes in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Nowadays, research is being conducted on the use of low and high frequency ultrasound in disinfection of sewage and sewage sludge on an increasing scale. They confirm the effectiveness of ultrasonic waves in destroying microorganisms [8,16,17,45,46].…”
Section: Membrane Methodssupporting
confidence: 58%
“…Nowadays, research is being conducted on the use of low and high frequency ultrasound in disinfection of sewage and sewage sludge on an increasing scale. They confirm the effectiveness of ultrasonic waves in destroying microorganisms [8,16,17,45,46].…”
Section: Membrane Methodssupporting
confidence: 58%
“…Ultrasonic technology can be used also to treat various kinds of WWs. For example, Vázquez-López et al (2019) reported on the efficient removal of microbiological parameters, biochemical oxygen demand, chemical oxygen demand, and total phosphorous with US (200 W, 24 kH). However, for WW treatment purposes highpower US devices are used, which can induce cavitation phenomena (Gao et al, 2014), and the generation of H• and OH• radicals, which contribute to the oxidation of microbial cells and chemical compounds (Vázquez-López et al, 2019).…”
Section: Physical and Chemical Parametersmentioning
confidence: 99%
“…Ultrasound has been successfully applied to inactivate pathogens and remove contaminants present in wastewater (Vázquez-López et al, 2019), as well as for the hydrolysis of activated sludge (Al-Hoqani et al, 2022). Ultrasound transducers transform electrical current into mechanical energy and generate mechanical vibrations and acoustic cavitation (the phenomenon of growth and collapse of bubbles due to the action of acoustic waves).…”
Section: Introductionmentioning
confidence: 99%